2018
DOI: 10.3390/medicines5030089
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Myrtus communis L. and Myrtus nivellei Batt. & Trab. Extracts: A Brief Review

Abstract: Myrtus communis L. (myrtle) and Myrtus nivellei Batt. & Trab. (Saharan myrtle) have been used in folk medicine for alleviating some ailments. M. communis is largely distributed in the Mediterranean Basin, whereas M. nivellei is confined in specific zones of the central Saharan mountains. The chemical composition and antioxidant activity of berry and leaf extracts isolated from myrtle are deeply documented, whereas those isolated from Saharan myrtle extracts are less studied. In both species, the major groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 143 publications
4
42
0
4
Order By: Relevance
“…Both CL values significantly decreased with MC treatment, similar to recent reports (Hayder et al, 2004;Hennia et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Both CL values significantly decreased with MC treatment, similar to recent reports (Hayder et al, 2004;Hennia et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, similar to previous reports (Escobar et al, 2009;Sen et al, 2016Sen et al, , 2017, the study results showed that MC treatment exerted a notable reduction in lipid peroxidation and an increase in GSH levels. This can be explained by the fact that M. communis has a strong free radical scavenging capacity, as shown previously (Hayder et al, 2004;Hennia et al, 2018) and demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, these small molecules can be used as an adjuvant treatment beside conventional therapy in cancer, due to their ability to reduce cancer Biology 2020, 9, 57 2 of 8 cell viability without affecting the proliferation of normal healthy cells [4][5][6]. Myrtus communis L. has a large amount of galloyl derivatives, as flavonols, and tannins in its berries, seeds and leaves, exerting important antioxidant and antimutagenic activities [7,8]. In the presence of an intense stressor, cells activate specific responses and mechanisms of repair, in order to counteract senescence or cell death [9,10].…”
Section: Introductionmentioning
confidence: 99%